Christian Dickens. (4th January 2016) - Sanders, Andrew
Abstract : In September 1844 Charles Dickens had a vivid dream while he was staying at the Villa Peschiere in Genoa. He dreamed that he was 'in an indistinct place, which was quite sublime in its indistinctness' and he was visited by a spirit which wore blue drapery, 'as the Madonna might in a picture by Raphael', but which bore no resemblance to anyone he had known. He recognized a voice, however, and concluded that this was the spirit of his much loved sister-in-law, Mary Hogarth. The seventeen-year-old Mary had died in his arms on 7 May 1837, six years before she conjured herself up in Dickens's dream. At the time he had been distraught. For months after her death he had dreamed of her 'sometimes as a spirit, sometimes as a living creature, never with any of the bitterness of my real sorrow, but always with a kind of quiet happiness'. Those dreams had long ceased, but the new manifestation of Mary in Genoa was evidently of a different kind. He beheld this visionary Mary 'in a great delight, so that I wept very much, and stretching out my arms to it called it "Dear."' He then entered into a dialogue with the spirit. 'Oh! give me some token that you have really visited me!', he pleaded.'Form a wish', the spirit replied. Dickens then asked that Mary's mother might be released from 'great distresses' and he was told that this would be so. He then posed a new question: 'What is the True religion?' The spirit seems to have hesitated, and Dickens blurted out:'Good God … You think, as I do that the Form of religion does not so greatly matter, if we try to do good? – or' (the ghost still hesitated) 'perhaps the Roman Catholic is the best? Perhaps it makes one think of God oftener, and believe in him more steadily?' '"For you, " said the spirit, full of such heavenly tenderness for me, that I felt as if my heart would break; "For you, it is the best!"' Dickens then woke up, with tears running down his cheeks.